In vivo morphogenesis and in vitro regeneration of Crocus sativus L. / Nordiyanah Anuar - Nordiyanah, Anuar (2021)
Thepresent research aimsto investigate the morphogenesisof CrocussativusL.grownin vivo andalso in vitroregeneration of this valuable crop forthefirst timein Malaysia.Duringin vivostudies, temperatureand growing substrateswereproven to significantlyaffect the growth performanceof C. sativuswhetherduring thevegetative or floweringphases. C. sativusrequiredaspecifictemperaturesetting and developed best in asequenceofhigh temperatureduring corm germination to lowertemperatureduringflower initiation. Theoptimumtemperatureforflower formation was at 16°Cprovidedthat the corms weregerminated at ahigher temperaturein therangeof 23°Cto 30°C. A very low temperature(10°C)during the dormancy stage, hamperedthe next stageofflower formation. This studyalso revealedthat C. sativuswas very wellgrownin 100%vermiculite as the plants produced biggercormlets with diameterof morethan 2.5 cmwith amean weightof 6.17 ± 0.11g.Thefloral phases of C. sativus though had limited references, was successfully described in detail in the present studywherebyunderfavourabletemperatureand best-growing media, the floral phaseslasted about 9 daysstartingfromthe beginning of flower cataphyll (BBCH51)until the end of flowering (BBCH69). At the full flowering stage (BBCH65), C. sativushad the greatest amount ofanthocyanin (257.33 ± 0.28 mg/100g) and the longest stigmas (3.64 ± 0.05 cm)for high yield recovery.An efficient in vitroregenerationprotocol was also successfullydeveloped for C. sativus via direct regeneration and somaticembryogenesis. Corm explant was the mostresponsiveexplant for direct regeneration and exhibited the optimumregenerationcapabilityin Murashigeand Skoog (MS)mediasupplemented with combination of 3 mg/l6-benzylaminopurine(BAP)and 1 mg/l naphthaleneaceticacid(NAA), while sprout and leaf explants failedto formcomplete plantlet.Complete regeneration with microcormletswas also achieved from whole, small-sized corm explant in the combination of 0.5 mg/l BAP and 0.5 mg/l NAA with anaverageof 5.73± 0.21 shoots,3.27 ±0.13 roots and 2.23 ± 0.10 microcormlets.In vitroflowering of C.sativus, though seldomlyreported in the literature, was achieved underinfluenceof 0.5mg/l triacontanol (TRIA)with 20%regeneration frequency. Somatic embryogenesiswas successfully established from corm-derived callusunder influenceof0.5 mg/lBAPwith maximum numberof microshoots (9.97 ±0.29)even though the earlier embryoproliferation phaseshowed moderatecallus multiplicationrate. Thecallus-derivedmicroshoots also yielded the optimumpercentageof microcormlets (83.33 ± 6.92%) with theaddition of 40 mg/l adenine sulphate(AdS). Theplantlets withmicrocormletswereacclimatizedin vermiculiteanddisplayed normal phenotypesimilar tothe motherplant. As saffron is ahighly expensive spiceproduced by C. sativus, in vitroregeneration protocols developed inthis studyalong withthein vivomorphogeneticproperties,has laid afoundation forfurther studies to develop appropriate technologyfor its commercial cultivation in Malaysia.